Predictive value of hypocalcemia in the diagnosis of acute respiratory failure in COVID-19 in a second-level care hospital - Santana-Téllez, Tomás Noel (2021)
Objective. To demonstrate the validity of hypocalcemia to predict the severity of respiratory failure in patients with COVID-19. Materials and methods. Prospective cohort-type study in 267 patients hospitalized in the Intermediate Care Unit of Hospital II EsSalud Pucallpa, between January and June 2021. Demographic, clinical and laboratory data were extracted from individual medical records. Multivariate analysis was used to identify variables associated with acute respiratory failure. Results. Of the 267 patients, 61% had hypocalcemia on admission. In this group, dry cough, fatigue and chest pain predominated; fever and dyspnea in all patients. The main comorbidity was obesity. Both respiratory rate ≥ 30 bpm and SaO2 ≤ 93% were more frequent in this group. There was an inverse relationship between hypocalcemia and the elevation of certain parameters considered inflammatory markers; in addition to a higher rate of abnormal PaFiO2. There was a good concordance between hypocalcemia and PaFiO2 results (Cohen’s Kappa index = 0.63). Conclusions. Hypocalcemia can be considered a predictor of severe respiratory failure in patients with COVID-19.